Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.7717/peerj.1950
|View full text |Cite
|
Sign up to set email alerts
|

Genome sequencing and analysis of the first complete genome ofLactobacillus kunkeeistrain MP2, anApis melliferagut isolate

Abstract: Background. The honey bee (Apis mellifera) is the most important pollinator in agriculture worldwide. However, the number of honey bees has fallen significantly since 2006, becoming a huge ecological problem nowadays. The principal cause is CCD, or Colony Collapse Disorder, characterized by the seemingly spontaneous abandonment of hives by their workers. One of the characteristics of CCD in honey bees is the alteration of the bacterial communities in their gastrointestinal tract, mainly due to the decrease of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
12
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 79 publications
3
12
1
Order By: Relevance
“…Apiaries located in Mottola and Valenzano showed the highest diversity at both the species and strain levels, although a relative high diversity at the strain level was found among all the five geographical locations, as shown by RAPD-PCR and phenotypic microarray analyses. Consistent with this finding, a polymorphism at strain level has been previously described in L. kunkeei and F. fructosus (53)(54)(55). Representative FLAB strains of each cluster group obtained by combined random amplification of polymorphic DNA patterns were phenotypically characterized using the OmniLog phenotype microarray (PM) Technology (Biolog).…”
Section: Discussionsupporting
confidence: 79%
“…Apiaries located in Mottola and Valenzano showed the highest diversity at both the species and strain levels, although a relative high diversity at the strain level was found among all the five geographical locations, as shown by RAPD-PCR and phenotypic microarray analyses. Consistent with this finding, a polymorphism at strain level has been previously described in L. kunkeei and F. fructosus (53)(54)(55). Representative FLAB strains of each cluster group obtained by combined random amplification of polymorphic DNA patterns were phenotypically characterized using the OmniLog phenotype microarray (PM) Technology (Biolog).…”
Section: Discussionsupporting
confidence: 79%
“…Six of the 10 isolated Lactobacillus species identified in the study had been previously reported as honey bee endophytes including L. plantarum , L. buchneri , L. gasseri , L. fermentum , L. pentosaceus and L. sanfranciscensis . These Lactobacillus species are linked with bee health due to their antimicrobial properties, high lactic acid yield and biofilm formation, among others …”
Section: Discussionmentioning
confidence: 88%
“…As expected, oxytetracycline was one of the most inhibitory compounds in vitro , confirming the results of Vásquez et al ., who reported high sensitivity to antibiotics in Lactobacillus isolated from bees. In tolerant strains, this would be related to antibiotic resistance genes, as seen in L. sanfranciscensis , which is closely related genetically to L. kunkeei in which inhibition of growth was not significant. Thymol is well known for its antimicrobial properties .…”
Section: Discussionmentioning
confidence: 99%
“…While initial genome sequencing strategies embraced the traditional Sanger sequencing methods 25 , more advanced sequencing technologies that are collectively referred to as the Next Generation Sequencing (NGS) technologies have been eventually adopted 26,[33][34][35] . The genome sequencing of probiotic species until or before 2010 was accomplished by the traditional Sanger sequencing method and shotgun sequencing technique.…”
Section: Genomic Technologies In Probiotic Researchmentioning
confidence: 99%
“…lactis AD011 25,27 . Post 2010, NGS technologies have been adopted for genome sequencing with the prominent ones being 454 pyrosequencing technology, Illumina/ Solexa paired end sequencing technology, Ion Torrent sequencing technology, and Pacific BioSciences sequencing technology 26,[33][34][35] .…”
Section: Genomic Technologies In Probiotic Researchmentioning
confidence: 99%